Electronic assistive technology use in Australian shared supported accommodation: rates and user characteristics. (3rd October 2018) - Jamwal, Rebecca; Callaway, Libby; Farnworth, Louise; Winkler, Di
Abstract: Electronic assistive technologies (EATs) are fast becoming considered an essential component of everyday life. To date, there has been little research on the use of EAT by people living in shared supported accommodation (SSA), one of the major community-based housing options for people with disability (PwD) in Australia. This study aimed to (1) audit current EAT use by PwD living in SSA, (2) describe the impact of Internet access on EAT use, and (3) examine potential relationships between individual characteristics and EAT use. A customized survey administered with 32 house managers, representing 52 SSAs, gathered data on the EAT use of 254 people. Only 45.7% of residents used EAT, and devices available to the mainstream market were most frequently used. Access to home-based Internet was not a predictor of the number of devices in use. Disability type (congenital or acquired) was found to be significantly correlated with the number of devices in use, however, associations across a number of variables suggest complex mediational interactions. These findings provide an insight into the EAT use trends of PwD living in SSA, indicating that further work needs to be done to support the uptake and continued use of EAT by PwD Implications for Rehabilitation: Further work needs to be done to promote the uptake and use of electronic assistive technology (EAT) by people with disability (PwD). Personal characteristics and experiences need to be considered in the prescription of EAT to PwD, as these may explain variations in use between individuals.